PDGFRA gene rearrangements are frequent genetic events in PDGFRA-amplified glioblastomas - Ozawa, Tatsuya (Cold Spring Harbor Laboratory Press, 2010)
Gene rearrangement in the form of an intragenic deletion is the primary mechanism of oncogenic mutation of the epidermal growth factor receptor (EGFR) gene in gliomas. However, the incidence of platelet-derived growth factor receptor-α (PDGFRA) gene rearrangement in these tumors is unknown. We investigated the PDGFRA locus in PDGFRA-amplified gliomas and identified two rearrangements, including the first case of a gene fusion between kinase insert domain receptor (KDR) (VEGFRII) and the PDGFRA gene, and six cases of PDGFRA(Δ8, 9), an intragenic deletion rearrangement. The PDGFRA(Δ8, 9) mutant was common, being present in 40% of the glioblastoma multiformes (GBMs) with PDGFRA amplification. Tumors with these two types of PDGFRA rearrangement displayed histologic features of oligodendroglioma, and the gene products of both rearrangements showed constitutively elevated tyrosine kinase activity and transforming potential that was reversed by PDGFR blockade. These results suggest the possibility that these PDGFRA mutants behave as oncogenes in this subset of gliomas, and that the prevalence of such rearrangements may have been considerably underestimated.